7 - Book Reviews: Bela Balassa : Policy Reform in Developing Countries (Pergamon Press, Headington Hill Hall, Oxford, U.K. 1977 - 175 pp - Heinecke, P. (Africa Development, 1981)
P. Heinecke, Faculty of Administration, Ahmadu Bello University, Zaria, Nigeria.